2009
DOI: 10.1007/s10620-009-0905-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoclip-Assisted Resection of Large Pedunculated Colorectal Polyps: Technical Aspects and Outcome

Abstract: In our experience, endoclip-assisted resection is a safe alternative to endoloop for the resection of large pedunculated colorectal polyps when endoloop placement is difficult or impossible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 20 publications
3
30
1
Order By: Relevance
“…This is similar to study of Bafandeh et al (2008), Mirzaie et al (2012) and Hodadoostan et al (2010) in which they found rectum and sigmoid together the most common site of the lesions in Iranian patients with colon polyps. The same finding also observed in other studies in western countries by Zois et al (2011) and Luigiano et al (2010). In this study most prevalent type of polyps was adenomatous 78(34.7%).…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to study of Bafandeh et al (2008), Mirzaie et al (2012) and Hodadoostan et al (2010) in which they found rectum and sigmoid together the most common site of the lesions in Iranian patients with colon polyps. The same finding also observed in other studies in western countries by Zois et al (2011) and Luigiano et al (2010). In this study most prevalent type of polyps was adenomatous 78(34.7%).…”
Section: Discussionsupporting
confidence: 92%
“…8). [47][48][49] These nylon loops come in a preloaded sheath, which is placed through the endoscope working channel. They are mechanistically similar to standard polypectomy snares except that once deployed they remain around the target lesion and are no longer attached to the sheath.…”
Section: Detachable Snaresmentioning
confidence: 99%
“…Various endoscopic techniques have been developed to prevent postpolypectomy bleeding; these include the administration of a submucosal injection with an epinephrine solution (1:10000) in the base of any polyps, argon plasma coagulation, or mechanical hemostasis (using a detachable snare and/or endoscopic clip) [8], [9], [10]. The hemostatic effect of epinephrine has been widely demonstrated and it is often used to prevent bleeding following colonic polypectomy and enhancing complete resection, especially in large sessile polyps [11], [12].…”
Section: Introductionmentioning
confidence: 99%